Isolation and characterization of novel microsatellite markers for Avena sativa (Poaceae) (oat) - Wu, B.; Zhang, Z.; Chen, L.; He, M. (Wiley, 2012)
• Premise of the study: A new set of microsatellite primers was developed for Avena sativa and characterized to assess the level of genetic diversity among cultivars and wild genotypes.• Methods and Results: Using an enrichment genomic library, 14 simple sequence repeat markers were identified. The loci of these markers were characterized and found to be polymorphic in size among 48 genotypes of oat from diverse geographical locations. The number of alleles per locus ranged from two to eight, while the observed heterozygosity ranged from 0.031 to 0.75.• Conclusions: These newly identified microsatellite markers will facilitate genetic diversity studies, fingerprinting, and genetic mapping of oat. Moreover, these new primers for A. sativa will aid future studies of polyploidy and hybridization in other species in this genus.